Strategi Pengelolaan Lingkungan Melalui Tindakan Kolektif dalam Transformasi Program Inovasi Sosial â€œPertamina Betterâ€ ke Yuk Ikam Wan Kawal Umpat Kolaborasi Nyata (Yuk Kawal IKN) oleh Pertamina Patra Niaga DPPU Sepinggan Group - Ashari, Heri; Firaldy, Akhmad Taufiq; Puspaningtiyas, Nindya; Nordiansyah, Ulik; Gandarita, Anggit (HK-Publishing, 2022)
The concept of Corporate Social Responsibility (CSR) is one of the concepts implemented to realize good corporate governance, where the company not only thinks about the company's interests in achieving financial benefits but also participates in ensuring the sustainability of social and environmental aspects in the area around the company's operations. This CSR concept emerged as a form of corporate moral responsibility to the community and the sustainability of the surrounding environment. Furthermore, what underlies this concept is a company's production activities that directly or indirectly affect social, economic, and environmental changes in the area around the company. Pertamina Patra Niaga DPPU Sepinggan Group, one of the companies that have implemented the CSR concept for a long time, also seeks to realize this through various social innovation programs, one of which is the Pertamina Better Program. For this reason, this article seeks to investigate the extent of the environmental management strategy carried out by Pertamina Patraniaga DPPU Sepinggan through its social innovation program. The author collects data through field observations, interviews, and documentation. The data analysis used is interactive. As a result, the Pertamina Better Program, a community empowerment program in the environmental field, can contribute to environmental sustainability by taking collective action involving various stakeholders. Each stakeholder of this program contributes not only in the form of funds but also ideas, thoughts, time, and energy. The Pertamina Better program can run better when each stakeholder contributes to the program. This contribution has become a collective action for the Pertamina Better program.